Potential epigenetic mechanisms in psychotherapy: a pilot study on DNA methylation and mentalization change in borderline personality disorder - Quevedo, Yamil; Booij, Linda; Herrera, Luisa; Hernández, Cristobal; Jiménez, Juan Pablo (Frontiers in Human Neuroscience, 2022)
Genetic and early environmental factors are interwoven in the etiology of Borderline Personality Disorder (BPD). Epigenetic mechanisms, offer the molecular machinery to adapt to environmental conditions. There are gaps in the knowledge about how epigenetic mechanisms are involved in the effects of early affective environment, development of BPD and psychotherapy response. We reviewed the available evidence of the effects of psychotherapy on changes in DNA methylation and conducted a pilot study in a sample of 11 female adolescents diagnosed with BPD, exploring for changes in peripheral DNA methylation of FKBP5 gene, which encodes for a stress response protein, in relation to psychotherapy, on symptomatology and underlying psychological processes. For this purpose, measures of early trauma, borderline and depressive symptoms, psychotherapy outcome, mentalization and emotional regulation were studied. A reduction in the average FKBP5 methylation levels was observed over time. Additionally, the decrease in FKBP5 methylation observed occurred only in those individuals who had early trauma and responded to psychotherapy. The results suggest an effect of psychotherapy on epigenetic mechanisms associated with the stress response. The finding that epigenetic changes were only observed in patients with early trauma suggests a specific molecular mechanism of recovery. The results should be taken with caution given the small sample size. Also, further research is needed to adjust for confounding factors and include endocrinological markers and therapeutic process variables.